2022
DOI: 10.1136/bmjopen-2022-067203
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypes of non-alcoholic fatty liver disease (NAFLD) and all-cause mortality: unsupervised machine learning analysis of NHANES III

Abstract: ObjectivesNon-alcoholic fatty liver disease (NAFLD) is a non-communicable disease with a rising prevalence worldwide and with large burden for patients and health systems. To date, the presence of unique phenotypes in patients with NAFLD has not been studied, and their identification could inform precision medicine and public health with pragmatic implications in personalised management and care for patients with NAFLD.DesignCross-sectional and prospective (up to 31 December 2019) analysis of National Health a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…The majority of subjects fell into the average NAFLD phenotype, whereas 6% and 10% of the remaining subjects fell into phenotypes characterized by (1) high levels of anthropometrics, systolic blood pressure, and glucose (highest all-cause mortality), or (2) high levels of liver biomarkers and cholesterol, respectively. 152 Furthermore, recent studies have demonstrated that diet and lifestyle modifications, including sugar reduction, are more effective in decreasing intrahepatic fat in NAFLD patients who are carriers of the PNPLA3 I148M gene polymorphism versus noncarriers. 153 , 154 A tailored dietary approach that accounts for differences in clinical, genetic, and metabolic characteristics between responders and nonresponders to nutrition therapies for NAFLD, including sugar reduction, may be more effective than traditional lifestyle recommendations.…”
Section: Sugar Reduction and Precision Nutritionmentioning
confidence: 99%
“…The majority of subjects fell into the average NAFLD phenotype, whereas 6% and 10% of the remaining subjects fell into phenotypes characterized by (1) high levels of anthropometrics, systolic blood pressure, and glucose (highest all-cause mortality), or (2) high levels of liver biomarkers and cholesterol, respectively. 152 Furthermore, recent studies have demonstrated that diet and lifestyle modifications, including sugar reduction, are more effective in decreasing intrahepatic fat in NAFLD patients who are carriers of the PNPLA3 I148M gene polymorphism versus noncarriers. 153 , 154 A tailored dietary approach that accounts for differences in clinical, genetic, and metabolic characteristics between responders and nonresponders to nutrition therapies for NAFLD, including sugar reduction, may be more effective than traditional lifestyle recommendations.…”
Section: Sugar Reduction and Precision Nutritionmentioning
confidence: 99%
“…Nonalcoholic fatty liver disease (NAFLD) is a liver disorder characterized by hepatic steatosis exceeding 5%, without secondary causes. [ 1 ] NAFLD prevalence is rising worldwide, with a prevalence of 30% in China and 25% in the world. [ 2 , 3 ] NAFLD is a major cause of hepatic sclerosis, liver cancer, and other liver diseases, burdening patients and the health system.…”
Section: Introductionmentioning
confidence: 99%
“…NAFLD may increase the risk of cardiovascular disease, chronic kidney disease, and some specific cancers 2,3 . However, its impact on mortality is still controversial due to the difference in the study population's characteristics and the diagnosis method of NAFLD [4][5][6][7][8] . Most NAFLD-related mortality studies were based on western people or limited by highly selected patient populations 4,5,9,10 .…”
Section: Introductionmentioning
confidence: 99%